The role played by carbonate cementation in controlling reservoir quality of the Triassic Skagerrak Formation, Norway. (August 2017) - Cui, Yufeng; Jones, Stuart J.; Saville, Christopher; Stricker, Stephan; Wang, Guiwen; Tang, Longxun; Fan, Xuqiang; Chen, Jing
Abstract: Anomalously high porosities up to 30% at burial depth of >3000 m along with varying amounts and types of carbonate cements occur in the fluvial channel sandstone facies of the Triassic Skagerrak Formation, Central Graben, Norway. However, porosities of the Skagerrak Formation are lower in the Norwegian sector than in the UK sector. In this study, petrographic analysis, core examination, scanning electron microscopy, elemental mapping, carbon and oxygen isotope, fluid inclusion and microgeometry analysis are performed to determine the diagenesis and direct influence on reservoir quality, with particular focus on the role played by carbonate cementation. The sandstones are mainly fine-grained lithic-arkosic to sub-arkosic arenites and display a wide range of intergranular volumes (2.3%–43.7% with an average of 23.6%). Porosity loss is mainly due to compaction (av. 26.6%) with minor contribution from cementation (av. 12.1%). The carbonate cements are patchy in distribution (from trace to 20.7%) and appear as various types e.g. calcretes (i.e. calcareous concreted gravels), poikilitic sparite and sparry ferroan dolomite, and euhedral or/and aggregated ankerite/ferroan dolomite crystals. This study highlights the association of carbonate precipitation with the remobilisation of carbonate from intra-Skagerrak calcretes during early burial stage i.e. <500 m. During deeper burial, compaction is inhibited by carbonate cements, resulting high intergranular volume of up to 32% and 29% for fine- and medium-grained sandstones, respectively. Carbonate cement dissolution probably results from both meteoric water flow with CO2 during shallow burial, and organic CO2 and carboxylic acid during deep burial. The maximum intergranular volume enhanced by dissolution of early carbonate cements is calculated to 8% and 5% for fine- and medium-grained sandstones, respectively. Compaction continues to exert influence after dissolution of carbonate cements, which results in a loss of ∼6% intergranular volume for fine- and medium-grained sandstones. Reservoir quality of the Norwegian sector is poorer than that of the UK sector due to a lower coverage of clay mineral coats e.g. chlorite, later and deeper onset of pore fluid overpressure, lower solubility of carbonate compared to halite, and a higher matrix content. Highlights: Carbonate cements dissolution contribute to good reservoir quality. Intergranular volume of sandstones is preserved by carbonate cements. Carbonate cements are mainly sourced by calcretes. Carbonate cements dissolution results from both meteoric water and organic acid.